IDIOPATHIC FOCAL EPILEPSY WITH PSEUDOGENERALIZED SEIZURES (A CLINICAL CASE) - I. A. Sadekov; I. V. Sadekova; L. V. Petrenko; O. I. Tishkovetz (Русский журнал детской неврологии, 2015)
The authors presented the case report – the patient with idiopathic focal epilepsy with pseudogeneralized seizures is described – the special form of child's epilepsy described first by K.Yu. Mukhin (2006). Specific for this form of epilepsy clinical and electroencephalographic criteria are described. The authors underline the importance of correct and timely syndromological diagnostics for improvement of therapy efficacy and clarification of prognosis.